Growing Up Under Constant Light: A Challenge to the Endocrine Function of the Leydig Cells - Marinkovic, Dijana Z.; Medar, Marija L. J.; Becin, Alisa P.; Andric, Silvana A.; Kostic, Tatjana S. (Frontiers in Endocrinology, 2021)
Factors influencing Leydig cell maturity and the acquisition of functional capacity are incompletely defined. Here we analyzed the constant light (LL) influence on Leydig cells' endocrine function during reproductive maturation. Rats were exposed to LL from P21 to P90. Data were collected at juvenile (P35), peri/pubertal (P42, P49), and adult (P90) stages of life. Results proved the effect of LL on rats' physiology by changing of bimodal voluntary activity pattern into free-running. Additionally, the peripheral clock in Leydig cells changed in LL condition, indicating disturbed rhythm: the positive element (Bmal1) increased in pre-/pubertal but decreased in the adult period while negative elements (Per2 and Reverba) were increased. The effects of LL were most prominent in puberty: pituitary genes encoding gonadotropic hormones (Cga, Lhb, Fshb) decreased; serum corticosterone increased, while serum androgens and mass of testicular and sex accessory organs reduced; markers of Leydig cells maturity/differentiation (Insl3, Lhcgr) and steroidogenesis-related genes (Scarb1, Star, Cyp11a1, Cyp17a1) decreased; the steroidogenic and energetic capacity of the Leydig cell mitochondria decreased; the mtDNA copy number reduced, and mitochondrial dynamics markers changed: fusion decreased (Opa1 and Mfn2), and mitophagy increased (Pink1). In adults, the negative effect of LL on mitochondrial function and steroidogenic capacity persists in adult Leydig cells while other parameters reached control values. Altogether, results indicate that LL slows down Leydig cells' maturation by reducing the endocrine and energy capacity of cells leading to the delay of reproductive development.